2003
DOI: 10.1109/twc.2003.819025
|View full text |Cite
|
Sign up to set email alerts
|

Blind reception of multicarrier ds-cdma using antenna arrays

Abstract: Abstract-In this paper, an asynchronous, multicarrier directsequence code-division multiple-access (DS-CDMA) array receiver is proposed based upon blind, composite channel vector estimation. Due to the fact that the combined effect of all received paths is estimated, the total number of paths can be greater than the number of antennas in the receiver array. Furthermore, the proposed approach is not limited by multipath coherency. The receiver is classified as an interference cancelling zero-forcing receiver, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Multi-carrier CDMA systems are strong candidates for the next generation of wireless communications, because of their inherent ability to tackle frequency selective channels, while at the same time enjoying the advantages of spread-spectrum systems. An array system using multicarrier transmission is introduced in [22] and modelled with the use of the MC-STAR manifold vector (16) where . .…”
Section: A Examples Of Extended Array Manifoldsmentioning
confidence: 99%
“…Multi-carrier CDMA systems are strong candidates for the next generation of wireless communications, because of their inherent ability to tackle frequency selective channels, while at the same time enjoying the advantages of spread-spectrum systems. An array system using multicarrier transmission is introduced in [22] and modelled with the use of the MC-STAR manifold vector (16) where . .…”
Section: A Examples Of Extended Array Manifoldsmentioning
confidence: 99%
“…where R 11 is the covariance matrix of the desired user (assumed to be user 1, without any loss of generality) and R N +I is the covariance matrix of noise plus interference [10]. Therefore, the overall data covariance matrix is given by…”
Section: B Snir Out Performance Of Arrayed Mc-cdma Receiversmentioning
confidence: 99%
“…Joint spacetime processing schemes are discussed in [7] and [8]; however, it is assumed that the subchannels are frequency nonselective. In contrast, the authors of [9] consider an array MC-DS-CDMA system which is transmitted through a fully frequency selective radio channel. A blind zero-forcing (ZF) receiver is proposed which cancels both intersymbol interference (ISI) and MAI.…”
Section: Mmse Multiuser Detection For Array Multicarrier Ds-cdma In Fmentioning
confidence: 99%
“…It is claimed that both matrices can be found from the estimated composite channel vectors for all users . In [9], it was demonstrated that the composite channel vector for each user could be estimated in a quasistationary environment by using subspace techniques and applying the theorem of alternating projection [16], [17]. A modified, tracking version of this procedure is presented here to provide estimates under time-varying conditions.…”
Section: Blind Implementation Of the Modified Mmse Receivermentioning
confidence: 99%
See 1 more Smart Citation